2017
DOI: 10.1074/jbc.m117.786798
|View full text |Cite
|
Sign up to set email alerts
|

LGR5 receptor promotes cell–cell adhesion in stem cells and colon cancer cells via the IQGAP1–Rac1 pathway

Abstract: Leucine-rich repeat-containing G protein–coupled receptor 5 (LGR5) is a bona fide marker of adult stem cells in several epithelial tissues, most notably in the intestinal crypts, and is highly up-regulated in many colorectal, hepatocellular, and ovarian cancers. LGR5 activation by R-spondin (RSPO) ligands potentiates Wnt/β-catenin signaling in vitro; however, deletion of LGR5 in stem cells has little or no effect on Wnt/β-catenin signaling or cell proliferation in vivo. Remarkably, modulation of LGR5 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 58 publications
2
63
0
Order By: Relevance
“…We measured CK2 activity indirectly by using an antibody against the phospho-CK2 substrate (motif pS/pTDXE) to measure the amount of phosphorylated CK2 substrates. This method is widely used in literature to measure kinase activity, such as activity of the following kinases CK2 [ 16 , 49 , 50 , 51 , 52 ], AMPK [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], AMT/ATR [ 64 , 65 , 66 , 67 , 68 , 69 , 70 ], PKA [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ], and PKC [ 77 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Both CK2 knockdown and CX-4945 treatment inhibited the proliferation of CCA cells.…”
Section: Discussionmentioning
confidence: 99%
“…We measured CK2 activity indirectly by using an antibody against the phospho-CK2 substrate (motif pS/pTDXE) to measure the amount of phosphorylated CK2 substrates. This method is widely used in literature to measure kinase activity, such as activity of the following kinases CK2 [ 16 , 49 , 50 , 51 , 52 ], AMPK [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], AMT/ATR [ 64 , 65 , 66 , 67 , 68 , 69 , 70 ], PKA [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ], and PKC [ 77 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Both CK2 knockdown and CX-4945 treatment inhibited the proliferation of CCA cells.…”
Section: Discussionmentioning
confidence: 99%
“…LGR5 was reported to alter the actin cytoskeleton structure and increased cell-cell adhesion by coupling to the intracellular scaffold signalling protein. 28,31 The study suggested that the major function of LGR5 may be to promote strong intracellular adhesion among stem cells and to retain them within the crypt base to maintain homoeostasis in the intestinal epithelium. 31 Weakened adhesion between cancer cells may facilitate the formation of intraperitoneal-free cancer cells, which may lead to peritoneal metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…28,31 The study suggested that the major function of LGR5 may be to promote strong intracellular adhesion among stem cells and to retain them within the crypt base to maintain homoeostasis in the intestinal epithelium. 31 Weakened adhesion between cancer cells may facilitate the formation of intraperitoneal-free cancer cells, which may lead to peritoneal metastasis. Hence, this finding may explain the potential of LGR-negative tumours to cause peritoneal metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…GPR56 has been shown to induce activation of the small GTPase RhoA mediated through Gα12/13 to promote cell adhesion (13,20,(24)(25)(26). To examine if mutant GPR56 STP was fully functional, we utilized a GTPase pulldown assay that employs the Rho binding domain of the Rho effector, Rhotekin.…”
Section: Gpr56 Overexpression Activates Srf-re Independent Of the Stpmentioning
confidence: 99%
“…GPR56 has been shown to interact with proteins such as collagen III (24), transglutaminase 2 (TG2) (17), and progastrin (16); however receptor-specific ligands have yet to be fully validated. Several studies have established that GPR56 is coupled to the Gα12/13 class of heterotrimeric G-proteins to promote RhoA activation (13,22,(24)(25)(26). GPR56 overexpression has been shown to activate various signaling pathway response elements, including serum response element (SRE) and serum response factor response element (SRF-RE) that are likely regulated downstream of RhoA (20,21,25).…”
Section: Introductionmentioning
confidence: 99%